Impact of nasopharyngeal irradiation and gadolinium administration on changes in T 1 signal intensity of the dentate nucleus in nasopharyngeal malignancy patients without intracranial abnormalities - Tang, Rongbiao; Haacke, E. Mark; Zhang, Yibin; Wang, Qingrou; He, Naying; Chen, Ke‐min; Yan, Fuhua (Journal of magnetic resonance imaging, 2020)
Irradiation has been found to increase T signal intensity (SI) of the dentate nucleus (DN) by accelerating the gadolinium deposition in patients after multiple gadolinium-based contrast agent (GBCA) administrations. Several reports have focused on this phenomenon in patients with brain tumors; however, data in patients receiving irradiation with no intracranial abnormalities (NIAs) are lacking. To explore how nasopharyngeal irradiation affected SI changes on unenhanced T -weighted imaging (T WI) in the DN in nasopharyngeal malignancy (NPM) patients who presented with NIAs and who had multiple injection doses (IDs) of linear GBCAs. Single-center, retrospective, case-control study. In all, 132 subjects: 66 NPM patients, 66 matched controls. 1.5T and 3T/T WI, T WI, and fluid-attenuated inversion recovery (FLAIR). Radiation doses (RDs) were calculated by a radiotherapy technician. SIs were measured by a radiologist. The DN-to-cerebellar white matter (CWM) SI ratios and their relative percentage change (R ) were compared. Shapiro-Wilk test, paired t-test, independent t-test, Mann-Whitney U-test, Pearson and Spearman correlation. DN/CWM ratios or R from the NPM group were significantly higher than those from the control group (P < 0.001). No significant difference of DN/CWM ratios was found between the two groups (P > 0.05). Positive correlations between R , DN/CWM ratio, and the number of IDs were found in both the NPM and control groups (P < 0.01). The overall changes of DN/CWM ratio or R between NPM and control groups were higher for the higher-IDs subgroup (≥10) than for the lower-IDs subgroup (<10). Nasopharyngeal irradiation appeared to increase SI in T WI in NPM patients with NIAs and repeated GBCA administrations relative to control patients who also underwent GBCA administrations, especially when IDs ≥10. However, no significant association between R and RDs to the DNs was found. 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;51:250-259.